Drugs Loaded into Electrospun Polymeric Nanofibers for Delivery - Erick José Torres-Martinez; Graciela Lizeth Pérez-González; Aracely Serrano-Medina; Daniel Grande; Ricardo Vera-Graziano; Jose Manuel Cornejo-Bravo; Luis Jesús Villarreal-Gómez (Frontiers Media S.A., 2019)
The electrospinning technique is a useful and versatile approach for conversion of polymeric solutions into continuous fibers, ranging from a few micrometers (10-100 μm) to the scale of nanometers (10-100 nm) in diameters. This technique can be used in a vast number of polymers, in some cases after modifying them to the required properties. The high surface-to-volume ratio of the fibers can improve some processes like cell binding and proliferation, drug loading, and mass transfer processes. One of the most important and studied areas of electrospinning is in the drug delivery field, for the controlled release of active substances ranging from antibiotics and anticancer agents, to macromolecules such as proteins and DNA. The advantage of this method is that a wide variety of low solubility drugs can be loaded into the fibers to improve their bioavailability or to attain controlled release. This review presents an overview of the reported drugs loaded into electrospun polymeric nanofibers to be used as drug delivery systems. These drugs are classified by their applications in pharmacy.